Overexpression of Fto leads to increased food intake and results in obesity. - Church, C; Moir, L; McMurray, F; Girard, C; Banks, G; Teboul, L; Wells, S; Brüning, J; Nolan, P; Ashcroft, F; Cox, R (2010)
Genome-wide association studies have identified SNPs within FTO, the human fat mass and obesity-associated gene, that are strongly associated with obesity. Individuals homozygous for the at-risk rs9939609 A allele weigh, on average, ~3 kg more than individuals with the low-risk T allele. Mice that lack FTO function and/or Fto expression display increased energy expenditure and a lean phenotype. We show here that ubiquitous overexpression of Fto leads to a dose-dependent increase in body and fat mass, irrespective of whether mice are fed a standard or a high-fat diet. Our results suggest that increased body mass results primarily from increased food intake. Mice with increased Fto expression on a high-fat diet develop glucose intolerance. This study provides the first direct evidence that increased Fto expression causes obesity in mice.